Data Privacy in Cloud-assisted Healthcare Systems: State of the Art and Future Challenges. - Sajid, Anam; Abbas, Haider (Journal of Medical Systems, 2016)
The widespread deployment and utility of Wireless Body Area Networks (WBAN's) in healthcare systems required new technologies like Internet of Things (IoT) and cloud computing, that are able to deal with the storage and processing limitations of WBAN's. This amalgamation of WBAN-based healthcare systems to cloud-based healthcare systems gave rise to serious privacy concerns to the sensitive healthcare data. Hence, there is a need for the proactive identification and effective mitigation mechanisms for these patient's data privacy concerns that pose continuous threats to the integrity and stability of the healthcare environment. For this purpose, a systematic literature review has been conducted that presents a clear picture of the privacy concerns of patient's data in cloud-assisted healthcare systems and analyzed the mechanisms that are recently proposed by the research community. The methodology used for conducting the review was based on Kitchenham guidelines. Results from the review show that most of the patient's data privacy techniques do not fully address the privacy concerns and therefore require more efforts. The summary presented in this paper would help in setting research directions for the techniques and mechanisms that are needed to address the patient's data privacy concerns in a balanced and light-weight manner by considering all the aspects and limitations of the cloud-assisted healthcare systems.